White organic light-emitting diode (OLED) microdisplay with a tandem structure. Issue 4 (2nd October 2019) - Cho, Hyunsu; Byun, Chun-Won; Kang, Chan-Mo; Shin, Jin-Wook; Kwon, Byoung-Hwa; Choi, Sukyung; Cho, Nam Sung; Lee, Jeong-Ik; Kim, Hokwon; Lee, Jeong Hwan; Kim, Minseok; Lee, Hyunkoo
Abstract : Microdisplay is a key technology for realizing augmented reality (AR) and mixed reality (MR) devices, which have attracted much attention of late. Even though the operating voltage in the tandem structure is higher than that in the single structure, 2-stack tandem OLED exhibited 20, 000 cd/m 2 at 9 V, which is compatible with CMOS circuit driving. Due to its top-emitting geometry with a tandem structure, the OLED device with a well-controlled thickness exhibited a white spectrum with (0.26, 0.26) color coordinates. The pixel density of the fabricated microdisplay panel with a white tandem OLED was about 2350 pixels per inch, and the active area of the panel was 0.7 inch diagonally. The resolution of the panel was 1280 × 1024, corresponding to SXGA, and the maximal luminance was 3, 000 cd/m 2 .